Case report: Ultrahypofractionated palliative breast radiotherapy for a fungating invasive mammary carcinoma - Hong, Yejun; Nixon, Nancy; Cao, Jeffrey Q.; Lee, Sangjune Laurence (Frontiers in Oncology, 2023)
Introduction: Palliative radiotherapy for symptomatic and intact breast tumors must balance convenience, efficacy, and risk of acute toxicity. This case report presents a patient with metastatic breast cancer and an intact fungating primary tumor, treated with a novel ultrahypofractionated radiation therapy schedule. Presentation: The patient presented with a large, purulent, ulcerated left-sided breast mass. She was treated with an ultrahypofractionated radiation therapy, 26 Gy in 5 consecutive daily fractions, with sequential palliative chemotherapy. This resulted in a minimal toxicity profile and significant reduction of tumor burden and symptoms. Conclusion: This case report overall illustrates the efficacy of the ultrahypofractionated dose-fractionation schedule for the palliation of intact symptomatic breast tumors while minimizing treatment burden.